2003
DOI: 10.1093/ageing/afg081
|View full text |Cite
|
Sign up to set email alerts
|

Medication use and falls in community-dwelling older persons

Abstract: These results are based on a Canadian population-based study with a large community sample. The study found that taking certain medications were independent predictors of sustaining an injurious fall in our elderly population - in addition to the risk associated with their medical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
7
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 16 publications
9
75
7
3
Order By: Relevance
“…Despite making references to polypharmacy, five studies did not include a definition. However, polypharmacy was not the primary theme of these studies (9, 11, 19, 20). All but two papers identified links between polypharmacy and falls.…”
Section: Resultsmentioning
confidence: 99%
“…Despite making references to polypharmacy, five studies did not include a definition. However, polypharmacy was not the primary theme of these studies (9, 11, 19, 20). All but two papers identified links between polypharmacy and falls.…”
Section: Resultsmentioning
confidence: 99%
“…(13,14) Conversely, a large study of over 11,000 patients failed to find an increased risk of falls in patients with cancer when falls were ascertained using administrative data. (34) Thus, the method of falls ascertainment may impact the results.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 28%–35% of people aged 65 years and older fall each year [2], and a study found that fall-related trauma accounts for 5.3% of all hospitalisations in this age range [3]. The risk of falls is multifactorial, and medications are modifiable extrinsic risk factors [4, 5]. Meta-analyses and systematic reviews have reported that some classes of medications, such as benzodiazepines (BZDs), increase the risk of falls in older people [68].…”
Section: Introductionmentioning
confidence: 99%